PENGARUH GAYA KEPEMIMPINAN KEPALA MADRASAH DAN MOTIVASI KERJA TERHADAP KINERJA GURU MADRASAH TSANAWIYAH DI KECAMATAN KALIWUNGU KABUPATEN KUDUS The Influence Of Madrasah Head-Master And Work Motvation On The Madrasah Tsanawiyah’s Head Master Performance In Kaliwungu Sub-District Kudus - Noor Miyono; Rakhmat Basuki (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2016)
Teachers play important roles in the success of the performance of school / madrasah. Teacher performance reflects the professionalism of teachers in performing their duties to achieve the educational goals. Teacher performance is influenced by several factors, both internal and external, the head master’s leadership style and teacher motivation are important variables among other factors that can affect the performance of teachers. Problems of this study are; (1) the influence of the headmaster’s leadership style on teacher performance, (2) the influence of motivation to work on teacher performance, (3) the influence of the head-master’s leadership style and motivation to work on teacher performance at Madrasah Tsanawiyah in Kaliwungu sub disctric, Kudus. Population of this gresearch are 241 teachers of Madrasah Tsanawiyah in Kaliwungu sub district Kudus, and there are 150 selected teachers as the sample. The selection is used proportional random sampling method. Data was gathered through questioner. SPSS for Windows Version 16 is applied to analyze validity and reliability of the instrument, and data (regression and lutiple regression). The results show that (1) the head-master’s leadership styles have strong influence on the teacher performance (69.3%), (2) teachers’ motivation has strong on teacher performance (72.7%), (3) the headmaster leadership style and motivation have strong influence on the performance of teachers Madrasah Tsanwiyah in Kaliwungu sub-district, Kudus (77.9%).